Effects of the sliaa9 Mutation on Shoot Elongation Growth of Tomato Cultivars - Abe-Hara, Chihiro; Yamada, Kohji; Wada, Naoki; Ueta, Risa; Hashimoto, Ryosuke; Osakabe, Keishi; Osakabe, Yuriko (Frontiers in Plant Science, 2021)
Tomato INDOLE-3-ACETIC ACID9 (SlIAA9) is a transcriptional repressor in auxin signal transduction, and SlIAA9 knockout tomato plants develop parthenocarpic fruits without fertilization. We generated sliaa9 mutants with parthenocarpy in several commercial tomato cultivars (Moneymaker, Rio Grande, and Ailsa Craig) using CRISPR-Cas9, and null-segregant lines in the T1 generation were isolated by self-pollination, which was confirmed by PCR and Southern blot analysis. We then estimated shoot growth phenotypes of the mutant plants under different light conditions. The shoot length of sliaa9 plants in Moneymaker and Rio Grande was smaller than those of wild-type cultivars, and the growth rates were higher under normal light conditions than those in low light conditions, whereas there wasn’t clear difference between the mutant of Ailsa Craig and the wild-type under both light conditions. On the contrary, sliaa9 mutants of young seedlings in Ailsa Craig exhibited altered photomorphogenesis in hypocotyl growth, while the other cultivars didn’t show apparent changes in this phenotype. Fruit production and growth rates were similar among the sliaa9 mutant tomato cultivars. These results suggest that control mechanisms involved in interaction of AUX/IAA9 and lights condition in elongation growth differ among commercial tomato cultivars.